Peran Pendidikan Dalam Membentuk Kesadaran Bela Negara di Kalangan Generasi Muda Indonesia - Irwan Triadi; Lia Agustina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
It is very important to instill state defense awareness to all citizens, especially the millennial generation as they are the successors and inheritors of the continuity of the life of the nation and state. This will help defend the country from internal and external threats, both military and non-military. Education is crucial in state defense as it helps the younger generation understand the history, principles and commitment to protect the country's sovereignty. Through education, students can understand the importance of maintaining national unity and integrity and become development actors that benefit the community and the country. The research that will be used in this paper is normative research with a perspective approach through ideology, laws, and phenomena. The purpose of this paper is to determine the extent to which formal education in Indonesia contributes to shaping state defense awareness among the younger generation, investigate the factors that influence understanding and awareness of state defense, analyze the implementation of the national education curriculum, provide recommendations for improving the education system. The benefit of this paper is to provide in-depth insight into the role of education in shaping a strong understanding of the concept of state defense among the younger generation.